A systematic review on characteristic and sub-characteristic for sustainable service-oriented architecture towards long living software - Ahmad, Ruzita; Hussain, Azham; Baharom, Fauziah (American Scientific Publishers, 2016)
The credibility of integration application such as Service-Oriented-Architecture (SOA) can ensure the achievement towards software sustainability in growing the accountability, reliability and functionality of software systems.The needs to recognize the element involved in sustainable SOA to support software development is significantly required.This paper is to investigate the state-of-the-art of sustainable SOA by identifying their important features and structuring into three dimensions of sustainability.The Systematic-Literature-Review (SLR) is used to achieve the objective in this study as to find the holistic understanding and views of sustainable SOA, including the recent processes, activities, performance, and limitations that relates to the importance of characteristic and sub-characteristic towards software sustainability. The investigation is based on 9,100 articles in the first iteration of databases that relates to the sustainable SOA. Currently, almost 676 articles are selected and only 49 articles are relevant in supporting the body of knowledge in this study.